Pengaruh Jenis dan Konsentrasi Aditif Terhadap Karakteristik Faktis Coklat dari Minyak Jarak Pagar - Santi Puspitasari (Eksergi)
Processing aid is an important chemical which is added to the rubber compound preparation. This ingredient will facilitate rubber mixing with other rubber chemicals. Brown factice is a processing aid used in the rubber article industries, especially in the rubber hose manufacture. This material is synthesized by polymerization of vegetable oil with sulfur at certain temperature. This reaction produces a crosslinking of the triglyseride molecules connected by sulfur. The crosslink causes the brown factice texture become elastic or rubberlike. The condition of the polymerization reaction and the compotition of reactant affect the brownfactice quality. The classification of brown factice is based on its visual and chemical  properties. The aim of the research was to study brown factice formulation which produce the optimum polymerization condition and the best quality of brown factice. In this experiment the brown factice was synthesized from Jatropha curcas oil at the laboratory scale using TMTD and ZDEC accelerators, by 1.0 pho dosage. The polymerization was conducted at 140oC on 30.0 pho of sulphur, while the ZnO and Na2CO3 dosage was varied at 0.25 and 0.50 pho. The reaction time, temperature, and exothermic step were observed conscientiously during the reaction. The brown factice rendemen was calculated and its quality was characterized. The result showed that the condition of the polymerization reaction using ZDEC and TMTD as  accelerator was not significantly different, but the quality of brown factice using ZDEC was better than TMTD (brighter color, lower free sulphur content, and acetone extract content). The best quality of  brown factice was obtained from the formulation of ZDEC as accelerator, 0.5 pho of ZnO and 0.5 pho of Na2CO3.